2013
DOI: 10.1007/s10816-013-9182-7
|View full text |Cite
|
Sign up to set email alerts
|

A Recreation of Visual Engagement and the Revelation of World Views in Bronze Age Scotland

Abstract: It has already been empirically verified that for many Bronze Age monuments erected in Scotland between 1400-900 BC, there was a concerted effort on behalf of the builders to align their monuments to astronomical bodies on the horizon. It has also been found that there are two common sets of complex landscape and astronomical patternings, combining specific horizon qualities (like distance and elevation) with the rising and setting points of particular astronomical phenomena. However, it has only been very rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(36 citation statements)
references
References 47 publications
1
35
0
Order By: Relevance
“…These above findings, along with the examination of our 3D landscape reconstructions of each site, revealed that the sky and land are woven together to create a complex series of particular interactions at very particular times of the lunar and solar cycles (Higginbottom et al 2013). (Higginbottom et al 2013: 47-53;Higginbottom in preparation 'The world begins here, the world ends here: Mull' (GH3)).…”
Section: Standing Stone Landscapes In Bronze Age Western Scotland (3d)mentioning
confidence: 74%
See 3 more Smart Citations
“…These above findings, along with the examination of our 3D landscape reconstructions of each site, revealed that the sky and land are woven together to create a complex series of particular interactions at very particular times of the lunar and solar cycles (Higginbottom et al 2013). (Higginbottom et al 2013: 47-53;Higginbottom in preparation 'The world begins here, the world ends here: Mull' (GH3)).…”
Section: Standing Stone Landscapes In Bronze Age Western Scotland (3d)mentioning
confidence: 74%
“…This means that Callanish was built in very close chronological proximity to Stenness. This, and their similar structural elements relating to circularity and to the dead (Higginbottom in preparation, Connecting the Great Stone Circles of Scotland (GH1); Higginbottom et al 2013; Richards (a)…”
Section: Archaeological Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…It soon became apparent that in this case the sun would appear from behind the Nevis range on the shortest day of the year. That can hardly have gone unnoticed when so many earlier prehistoric monuments were associated with the solar cycle (Ruggles 1999, chapter 8;Higginbottom et al 2015). It seemed much more than a coincidence that one of the largest assemblages of early metalwork should be related to the highest summit in the British Isles.…”
Section: The Relationship Between Dail Na Caraidh and Ben Nevismentioning
confidence: 99%